2022
DOI: 10.1088/2634-4505/ac61f8
|View full text |Cite
|
Sign up to set email alerts
|

Piped water revenue and investment strategies in rural Africa

Abstract: Viable pathways to universal safely managed drinking water access in rural Africa involve a blend of infrastructure types, service delivery arrangements, and sources of finance. Priorities are shaped by institutional and economic barriers and are often based on assumptions regarding user demand and revenue sustainability. Improved understanding of how alternative approaches affect revenue generated from user payments can enhance long-term viability and repayment capacity of rural piped water services. We analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…39),40), 41) A study shows that the highest observed data on revenue from water sales after equipping PPMs more than tripled compared to the facilities before equipping PPMs. 39) However, Armstrong et al 40) indicated that the PPM approach is not associated with revenue advantages compared to the conventional PAYF approach. We assume that the difference between these two studies depends on whether the collected money by WUAs is monitored by a third party.…”
Section: (3) External Supportmentioning
confidence: 99%
“…39),40), 41) A study shows that the highest observed data on revenue from water sales after equipping PPMs more than tripled compared to the facilities before equipping PPMs. 39) However, Armstrong et al 40) indicated that the PPM approach is not associated with revenue advantages compared to the conventional PAYF approach. We assume that the difference between these two studies depends on whether the collected money by WUAs is monitored by a third party.…”
Section: (3) External Supportmentioning
confidence: 99%